VD_FINDINFO HC / 2011 / 299 vom 6. Juni 2011 - VD Tribunal cantonal (2011)
REJET DE LA DEMANDE, DROIT DE RÉPONSE, PROTECTION DE LA PERSONNALITÉ, MÉDIA, MÉDIA À CARACTÈRE PÉRIODIQUE | 28g al. 1 CC, 28g CC, 28h al. 1 CC, 28h al. 2 CC, 28h CC, 312 al. 1 CPC (CH)